Relationships between geomagnetic Ар-indeх and HRV and endocrine parameters in patients with dysfunction of the neuroendocrine-immune complex - Tserkovniuk, Ruslan; Gozhenko, Anatoliy; Korolyshyn, Tetyana; Ruzhylo, Sofiya; Kikhtan, Volodymyr; Fil, Vitalij; Anchev, Anatoliy; Zukow, Walery; Yanchij, Roman; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. Recently, on the example of two cohort of patients, we found that disturbances of the geomagnetic field cause a significant immediate modulating effect on the level of immune parameters in the blood. The data available in the literature give grounds for assumptions about the direct effect of disturbances of the geomagnetic field on immunocytes, and indirectly, through immunotropic neurotransmitters and hormones. Our hypothesis is as follows. Disturbances of the geomagnetic field are perceived by acupuncture points. The information obtained is transmitted to neurons and endocrinocytes, the mediators of which, in turn, affect immunocytes. The purpose of this study is to test this hypothesis. Material and methods. The object of observation were 21 men (24-63 y) and 20 women (30-72 y) with neuroendocrine-immune complex dysfunction. Each patient was tested twice with an interval of 4 days. Retrospectively we recorded the geomagnetic Ap-Index on the day of testing and during the previous 7 days, using resource https://www.spaceweatherlive.com/. Recorded the heart rate variability (HRV) parameters, determined the plasma level of cortisol, triiodothyronine and testosterone. Results. During the week, the average level of Ap-index ranged from 7 to 13 nT. Maximum coefficients of multiple correlation with HRV&Hormonal parameters were detected for Ap-index on 2 (R=0,506) and 7 (R=0,403) days before testing. The canonical correlation between Ap-indices for 7 days before and on the day of testing, and the HRV&Hormonal parameters is 0,766. In turn, the immune parameters are closely related to the HRV&Hormonal parameters (R=0,714). Conclusion. Disturbances of the geomagnetic field (Ap-index) causes a significant immediate modulating effect on the immune, HRV and endocrine parameters, apparently through acupuncture points as polymodal receptors of the ecoceptive sensitivity system.